Penghidupan Kembali Perpustakaan Sekolah Dasar Sebagai Bentuk Penguatan Gerakan Literasi di Sekolah - Vichaully, Yessi; Megawanti, Priarti; Yuniarti, Yeni (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2024)
The library is one of the important facilities in the school. The library itself provides reading resources and other information that can be utilized by teachers and students. The livelihood of libraries that have not been used for a long time is a form of strengthening literacy in schools. Good use of libraries in schools will improve students' literacy skills as well, such as by making activities that can be carried out in the library. With good library facilities, students' needs for reading and information materials will also be fulfilled properly. This study used a qualitative approach to description. This study explains what activities can be carried out in the library after revival is carried out as a form of strengthening the literacy movement in schools.